2021
DOI: 10.3390/su13073869
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of the Infrastructure of Marine Passenger Port Based on Synthesis of the Structure and Forecasting Development

Abstract: Passenger seaports are new starting-points of urban development. They form a new independent industry, become new incentives for improving urban infrastructure and increase the tourist attractiveness of the city itself and the region. In view of changes in passenger service processes, changes in route ferry and cruise networks, due to COVID-19, the heads of ports and terminals set new strategic tasks to determine the directions for infrastructure modernization and forecast development. The regions of the Adria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This provision also directly applies to the seaports of passengers as major centers of development of cruise and ferry lines, cruise industry and transport processes. On the basis of the authors' works [3,5,6], it can be concluded that by the 1980s, it became obvious that without proper research and analysis of seaport development, it is impossible to manage, design and forecast sea development of passenger ports effectively. Forecasting of development is one of the key areas as it allows us to obtain answers to such questions as: 1.…”
Section: Models and Methods Of Forecasting The Development Of "City-seaport Passenger Port" Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provision also directly applies to the seaports of passengers as major centers of development of cruise and ferry lines, cruise industry and transport processes. On the basis of the authors' works [3,5,6], it can be concluded that by the 1980s, it became obvious that without proper research and analysis of seaport development, it is impossible to manage, design and forecast sea development of passenger ports effectively. Forecasting of development is one of the key areas as it allows us to obtain answers to such questions as: 1.…”
Section: Models and Methods Of Forecasting The Development Of "City-seaport Passenger Port" Systemsmentioning
confidence: 99%
“…It is well known that theoretical approaches to port development have been developed over the years, during which various researchers attempted to explain the complex process of port development by proposing various models of a qualitative, descriptive nature. In the models considered by the authors [1][2][3][4][5][6], it was implied that the sea passenger port represents a certain stage of development of the main cargo port. However, today, the situation is quite different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of scientific papers [1][2][3][4][5][6][7][8][9][10][11][12][13] have been devoted to the research in the field of sea cruising. The works [1,2,5,6,11,12,13] provide the results of research into the impact of the COVID-19 pandemic on the functioning and development of sea cruising.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The works [1,2,5,6,11,12,13] provide the results of research into the impact of the COVID-19 pandemic on the functioning and development of sea cruising. Also in scientific works [3,4,7,8,9,10] justification and analysis of development of cruise transport and the industry as a whole are carried out. The team of authors Aleksandar Radic, Michael Lück, Amr Al-Ansi, Bee-Lia Chua, Sabrina Seeler, António Raposo, Jinkyung Jenny Kim and Heesup Han have considered important issues of sanitary and epidemiological standards on board liners to ensure passenger safety.…”
Section: Literature Reviewmentioning
confidence: 99%